2005
DOI: 10.1007/s10571-005-4956-5
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin A Aggravates Electroshock-Induced Convulsions in Mice with a Transient Middle Cerebral Artery Occlusion

Abstract: 1. To test whether an ischemic insult increases the susceptibility to cyclosporine A (CsA)-induced neurotoxicity, we examined the effect of CsA on the minimal electroshock-induced convulsions in mice treated with a transient middle cerebral artery occlusion (MCAO) for a short period (2 h). 2. This MCAO produced small to mid-sized infarcted regions in the cerebral hemisphere with increasing post-operative days. In MCAO mice, CsA (30 mg/kg, i.p.) elevated the incidence of minimal electroshock-induced convulsions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…[11][12][13] A laser Doppler probe (ALP-NC, Unique Medical, Osaka, Japan) inserted into the acrylic sheath was positioned over the left skull 2 mm posterior to the bregma and 6 mm to the left side of the midline. Baseline rCBF values measured before the occlusion were defined as 100%.…”
Section: Measurement Of Cerebral Blood Flowmentioning
confidence: 99%
“…[11][12][13] A laser Doppler probe (ALP-NC, Unique Medical, Osaka, Japan) inserted into the acrylic sheath was positioned over the left skull 2 mm posterior to the bregma and 6 mm to the left side of the midline. Baseline rCBF values measured before the occlusion were defined as 100%.…”
Section: Measurement Of Cerebral Blood Flowmentioning
confidence: 99%
“…On the basis of the results of our previous behavioral experiments (Shuto et al 1998(Shuto et al , 1999Fujisaki et al 2001Fujisaki et al , 2002Tominaga et al 2001Tominaga et al , 2002Yamauchi et al 2005), the dose of cyclosporin A in the present study was determined to be 50 mg/kg. Cyclosporin A or vehicle was administered (i.p.)…”
Section: Effect Of Cyclosporin a On Harmine-induced Tremors In Hepatementioning
confidence: 99%
“…In addition, we reported that cyclosporin A aggravates electroshock-induced convulsions in mice with transient occlusion of the middle cerebral artery (Yamauchi et al 2005) and that ovariectomy elevates the susceptibility to cyclosporin A-induced convulsions in rats (Tominaga et al 2001(Tominaga et al , 2002. These in vivo findings are considered to be due to the direct action of cyclosporin A being transported across the blood-brain barrier (BBB) in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Among patients with ischemic infarction, technetium-labeled diethylenetriamine penta-acetic acid can penetrate the BBB (Gumerlock 1989), suggesting that patients previously suffering from stroke or transient ischemic attack show partially damaged function of the BBB. Recently, we demonstrated that CsA aggravates electric shock-induced convulsions in mice with cerebral infarction (Yamauchi et al 2005). Considering these results together, we hypothesized that CsA transport into the brain might be increased due to the incomplete recovery of the BBB from ischemia and post-ischemic injury.…”
Section: Introductionmentioning
confidence: 93%